110 THE pre-operative 12 lead ECG; can it predict post-operative cardiac complications?. (22nd September 2015) - Payne, C J; Payne, A R; Gibson, S C; Bryce, G; Jardine, A; Berry, C; Kingsmore, D B
Abstract : Introduction: The 12 lead electrocardiogram (ECG) is a standard pre-operative investigation for patients undergoing major surgery. A number of recent publications have questioned the predictive value for post-operative cardiac risk. The aim of this study is to investigate the correlation between an abnormal ECG and a post-operative major adverse cardiac event (MACE) and mortality. Methods: A prospective single centre observational cohort study of 345 patients undergoing major non-cardiac surgery between January 2004 and August 2006 was performed. Patients underwent standard pre-operative assessment including an ECG. Screening for post-operative events was carried out with serial ECG and troponin measurement. Primary end-points were MACE (cardiac death and non-fatal myocardial infarction) and all-cause mortality. Results: Three hundred and forty-five patients were included in the study, performed between January 2004 and August 2006. 276 (80.0%) patients underwent a vascular procedure (aortic surgery 25.8%, lower limb bypass 29.8% and amputation 25.2%) and 69 (20.0%) patients underwent laparotomy. An abnormal ECG (Abstract 110 Table 1 ) was present in 141 (40.9%) patients. MACE was observed in 46 (13.3) patients, and 27 (7.8%) patients died in the post-operative period. Patients with an abnormal ECG had a higher incidence of MACE (22.0% vs 7.4%, p<0.001), and higher mortality rate (12.1% vs 9.8%, p=0.015). Univariate analysis shows that AF, strain and prolonged QTc interval predict post-operative events. Multivariate analysis of clinical variables and ECG abnormalities showed that strain, prolonged QTc and hypertension independently predicted post-operative MACE. Conclusion: This study shows that ECG abnormalities were more predictive than traditional clinical variables for post-operative MACE, and therefore confirms that an ECG remains a useful adjunct in pre-operative assessment before surgery. An abnormal ECG confers a threefold increase risk of post-operative MACE. This may allow improved pre-operative optimisation and enhanced peri-operative care to reduce the event rates.